ANALISIS KANDUNGAN ZAT GIZI MAKRO DAN MIKRO PADA MI KERING IKAN PATIN - Fitriani Fitriani; Yuniarti; Ria Ambarwati (ARGIPA (Arsip Gizi dan Pangan), 2023)
Noodle products consumed by the public are currently not supported by a balanced nutritional value. Dried catfish noodle product with pumpkin flour substitution has high protein content and low water content according to SNI, but this product has not been analyzed for macro and micro nutrients. The aim of the study was to analyze the macro and micro nutrient content in dried catfish noodles substituted with pumpkin flour. This type of research is pre-experimental design with a one-shot case study design. Analysis of macronutrients using proximate analysis, Kjeldahl method. Analysis of protein and micronutrients used the AAS method. Dry noodles have a water content of 7.51% - 9.68%, ash content 1.46% -2.84, energy 383.005 kcal, protein 7.78 grams, fat 4.865 grams and carbohydrates 67.025 grams. The need for macronutrients aged 4-6 years when consuming 1 serving contributes 13.67% energy, 35.56% protein, 4.87% fat and 15.23% carbohydrates. Dried catfish noodles substituted with pumpkin flour also contain micronutrients consisting of 2.155 mg zinc, 4.16 mg iron, 36.87 mg calcium, 0.01% albumin and 4,066.88 µg beta-carotene. Referring to SNI and BPOM, this dry noodle is a high-protein processed food and a source of vitamins and minerals for zinc, iron and beta-carotene. While the levels of calcium and albumin do not meet BPOM requirements because the nutrient content is <15% ALG.